What about Exotic Species? Significance of Remains of Strange and Alien Animals in the Baltic Sea Region, Focusing on the Period from the Viking Age to High Medieval Times (800–1300 CE) - Ulrich Schmölcke (Heritage, 2022)
During the Viking era and the Middle Ages, in the Baltic Sea area, the remains of alien animal species are found rarely but recurrently. These species, which were previously widely distributed in other regions, were originally considered “exotic” by the local people of the Baltic Sea region. Conversely, “exotic” was also used to describe the last local specimens of those indigenous species that had become very rare over time. Other categories of exotic animals can be defined: the first specimens of domesticated animals seen in an area, and mythical species whose existence was generally, but erroneously, assumed. In the present paper, the evidence of selected exotic species in the Baltic Sea area is analyzed with regard to both their cultural–historical and ecological significance. Many exotic specimens were used for social and hierarchical display, illustrating the individual’s sophistication and broad knowledge of the world, their wealth, and their supra-regional influence. As a result, before Christianization, these species became part of burial rites. At the same time, some of these species became or were already integral parts of the fauna of the Baltic Sea region. Some newly immigrated species were welcomed by the people, while others were considered pests. “New”, initially exotic, species formed the basis for the purely anthropogenic urban ecosystems that emerged during this period. Meanwhile, other, formerly common, species had become “exotic” because of their increasing rarity; when they became extinct, they left significant gaps in the biocoenoses wherein they were interconnected. These ecological effects, as well as some of the socio-cultural characteristics of exotic species, find parallels in modern times.